Bounded risk per unit cost index constraint for sequential estimation of the mean in a two-parameter exponential distribution. Issue 3 (30th September 2022) - Mahmoudi, Eisa; Nemati, Zahra; Khalifeh, Ashkan
Abstract: In this article, the two-stage sequential sampling procedure is proposed to estimate the mean of an exponential distribution under the modified square error loss function. The main aim of the article is to consider the associated risk per unit cost function by bounding it from above with a fixed preassigned positive number, ω . We provide the exact distribution of the total sample size, explicit formulas for the mathematical expectation of the r th power of the total sample size, the expected value and mean squared error of the maximum likelihood estimate of the scale, and mean parameters of the exponential distribution under the two-stage sequential procedure. The performances of the proposed methodologies are investigated with the help of simulations. In the end, we supplement with extensive sets of data analysis via computer simulations, validating that the two-stage sequential method performs very well. Finally, using a real data set, the procedure is clearly illustrated.